PERAN FINANSIAL TEKNOLOGI TERHADAP DAYA SAING UMKM DI KOTA PANGKALPINANG SELAMA MASA PANDEMI COVID 19 - Nanang Wahyudi; Darus Altin1; Vebstasvili (Universitas Muhammadiyah Bengkulu, 2023)
This study aims to analyze the competitiveness of the role of Financial Technology (Fintech) in MSMEs in Pangkalpinang City. This study used qualitative descriptive studies and Importance Performance Analysis analysis. The data collection method is carried out by document analysis and interviews. The results showed that Financial Technology helps MSME players in efficiency and effectiveness in the payment system, but in digital banking and digital insurance has not yet been implemented optimally.